The new mode of marine planning in the UK: Aspirations and challenges. (January 2015) - Scarff, Gavin; Fitzsimmons, Clare; Gray, Tim
Abstract: Since 2009, there has been a shift in UK marine governance with the Marine and Coastal Access Act in which a core mechanism is marine planning, designed to replace a fragmented, ad hoc, and bureaucratic process of marine management with a strategic, integrated, and centralised system. This shift has been justified by the UK government as a more efficient procedure for delivering sustainable development (SD), which is the overarching objective of UK environmental policy. This article, which is based on data from key informant interviews and secondary sources, analyses the shift to understand its aspirations and the challenges facing it. The issues focused on include its holistic approach; its centralising tendencies; its streamlining processes; and its implicit commitment to renewable energy. In these four issues there are tensions between aspirations and challenges, and the conclusion is that the success of the new mode of marine governance depends on satisfactorily resolving these tensions.